Entrepreneurship through Khejri Technology - Gurjar, P S; Samadia, D K; Ram, H; Verma, A K; Kumawat, K L; Berwal, M K; Sarolia, D K (Indian Horticulture, 2024)
Khejri (Prosopis cineraria) is a versatile tree of Thar Desert and well-known for its nutritious immature green pods (sangri) and leaf-fodder (loong), and exerts favourable effect on soil and environment in the arid and semi-arid areas of north-western India. Khejri not only tolerates the extreme edaphoclimatic conditions but the lush-green plants also bear flowers and pods during peak summer months. ICAR-CIAH, Bikaner has made a series of technological interventions for its systematic promotion which includes clonal multiplication for uniform plantations, varietal improvement for high-quality harvest from thornless plants, orchard establishment models for maximizing resources efficiency, crop regulation to harvest both sangri and loong annually, value addition, packaging and marketing protocol for better income generation as nature’s resilient farming system approach.